In the Beginning was the Software Tool... - FARGE, ODILE (Hyperrhiz)
The digital environment constitutes a strong symbolic territory and gives the software tool a special importance. It allows the creator to pass from a profane world to a world where the language brings an incontestable power. And the practice (or not) of coding inevitably influences the production of the digital work. It conditions the relation with the software tool, which itself is based on the code. How do authors of digital literature seize this matter of the code to go beyond the proposals of the software tool, and what are the implications on programming practices? Since the software tool relies on the imaginary to enter in a relationship with the author of a work, do the imaginaries mobilized by the software tool or the code determine the trajectory of creation of a digital work? In this context, what responses does the author formulate to the machine or the software? In other words, are the implemented strategies the manifestation of an awareness of the statement of the software tool or even an expression of a specific culture? The essay also questions the role of Digital Literature through the prism of Digital Humanism. Humanism is primarily a critical posture that cannot be separated from freedom of expression or creativity. The recognition of cultural diversity sheds light on the humanistic vision that informs digital literature and shows how a critical and pedagogical approach is essential for an awareness of the rhetorical, and for defending and carrying the values and humanism of the digital model.